Navigating The Era of Disruption: Effective Da’wah in Non-Formal Education Institutions - Khotimatun, Siti; Hermanto, Agus; Yanti, Fitri; Rohmad, Rohmad (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2024)
The era of disruption marks significant changes in various aspects of life, including education. Da'wah through non-formal education (PNF), as one of the important pillars in character building and moral values, is faced with challenges to remain relevant and effective in delivering its da'wah. This journal aims to discuss effective da'wah strategies in PNF in the era of disruption. The methodology used in this research is a literature study by reviewing various scientific sources, such as journals, articles, and interviews as supporting data. The results showed that effective da'wah in PNF in the era of disruption is by utilizing information and communication technology such as social media to reach a wider audience and increase interactivity. However, this application needs to consider aspects of philosophical principles: principles related to the goals to be achieved in the da'wah process. Psychological principles: principles related to the human psyche, both da'i (preachers) and da'wah targets. Sociological principles: principles that discuss issues related to the situation and conditions of the target of da'wah, such as politics, society, and religion in the local area. With a compatible implementation strategy, PNF is able to become an institution that navigates the direction of da'wah to society, especially the younger generation.